The Impact Of Firm Size, Leverage, And Liquidity On Sustainability Report Disclosure With Profitability As Moderating Variable - Winda Islamiati; Dhini Suryandari (Jurnal Akuntansi Bisnis, 2020)
This study aims to examine the effect of firm Size, leverage, and liquidity on the level of sustainability report by using profitability as a moderating variable. Firm samples were gathered from Sri-Kehati Index of Indonesia Stock Exchange for the period of 2016-2019. Applying purposive sampling technique, as much as 56 observations are available for further analysis. Test of hypotheses were conducted by using moderated regression analysis (MRA). Results support hypothesis one suggesting larger firm size is associated with higher sustainability report disclosure. Meanwhile, hypothesis two is rejected suggesting that leverage has no effect on sustainability reports disclosure. The results of this study also reject third, liquidity has no effect on the disclosure of sustainability reports. As for moderating variable, the results show that profitability does not affect the relation between firm size, leverage, and liquidity with sustainability report discolure. Results of this study are expected to serve as a guideline for companies to assess the benefit of sustainability report disclosures. As for investors, the results may help investors in making investment decision.